2019
DOI: 10.1002/ejp.1412
|View full text |Cite
|
Sign up to set email alerts
|

Discharged and dismissed: A qualitative study with back pain patients discharged without treatment from orthopaedic consultations

Abstract: Background Consultation‐based reassurance for patients with low back pain (LBP) in primary care has been shown to be associated with patients' outcomes. Little is known about the role of reassurance in people with LBP consulting with orthopaedic spinal care teams. Reassurance may be important, especially in cases where surgery is not indicated and patients are discharged without treatment. Methods Semi‐structured interviews were conducted with 30 patients with chronic disabling musculoskeletal LBP who had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Communication between patients and community-practicing surgeons has shown that the majority of talking was conducted by surgeons, who typically used closed questions, and were limited and infrequent in their expression of empathy towards patients (Levinson & Chaumeton, 1999). In reference to providing explanations, orthopaedic surgeons have been shown to use a high level of jargon and offer explanations that patients find difficult to follow (Braeuninger-Weimer et al, 2019;Laerum et al, 2006). Other evidence suggests that orthopaedic surgeons show a tendency to focus mainly on technical aspects of care-giving, lack listening skills, are inconsistent in the terminology they use, frequently use medical jargon and express infrequent signs of empathy towards patients (Frymoyer & Frymoyer, 2002;Han & Pappas, 2018;Herndon & Pollick, 2002;Kampa et al, 2006;Kyle & Shaw, 2014;Levinson & Chaumeton, 1999;Levinson et al, 2013;Portalatín et al, 2018;Tongue et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Communication between patients and community-practicing surgeons has shown that the majority of talking was conducted by surgeons, who typically used closed questions, and were limited and infrequent in their expression of empathy towards patients (Levinson & Chaumeton, 1999). In reference to providing explanations, orthopaedic surgeons have been shown to use a high level of jargon and offer explanations that patients find difficult to follow (Braeuninger-Weimer et al, 2019;Laerum et al, 2006). Other evidence suggests that orthopaedic surgeons show a tendency to focus mainly on technical aspects of care-giving, lack listening skills, are inconsistent in the terminology they use, frequently use medical jargon and express infrequent signs of empathy towards patients (Frymoyer & Frymoyer, 2002;Han & Pappas, 2018;Herndon & Pollick, 2002;Kampa et al, 2006;Kyle & Shaw, 2014;Levinson & Chaumeton, 1999;Levinson et al, 2013;Portalatín et al, 2018;Tongue et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are no guidelines on what constitutes effective reassurance for such patients, or on how to deliver it (Oliveira et al., 2018), and it remains a neglected area of research (Linton et al., 2008). Reassurance is conceptualized as a set of practitioner's behaviours that aim to reduce patients concerns (Linton et al., 2008), and for back pain, research suggests that it includes components around data gathering and relationship building, but also clear explanations, a management plan, validation of the pain experience and where appropriate, positive messages aimed to increase self‐efficacy (Braeuninger‐Weimer et al., 2019; Pincus et al., 2013). Such reassuring behaviours may be particularly important when delivered by practitioners who believe they have no interventions left to try, often conceptualized as ‘end of the line’ consultations about possible spine surgery, because they aim to help empower patients towards self‐management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication style —Findings from a recent qualitative study suggests four key behaviours from clinicians that can help patients feel reassured 23…”
Section: How Should Practice Change?mentioning
confidence: 99%
“…5 Research suggests that these patients receive less reassurance and are less satisfied: instead of accepting the need to self-manage their problem, they feel dismissed, disbelieved and abandoned. 17 The findings from a prospective cohort study of 296 patients discharged from orthopaedic care without surgery suggest that better communication in consultations with orthopaedic spine clinicians might help reduce distress and unnecessary subsequent healthcare utilisation. 5 Effective reassurance necessitates engaging with patients and their concerns.…”
Section: Introductionmentioning
confidence: 99%